Trend of Presenters on The Ḥadīth of al-Isrāʾ wa al-Miʿrāj and Netizens’ Reflections in Selected Youtube Talks - Ishak Suliaman (Al-Bayān, 2022)
Abstract YouTube is one of digital platforms in spreading the ḥadīth to the public that known as netizen. The topic of al-Isrāʾ wa al-Miʿrāj is one of the popular talks in YouTube particularly among Malaysian Muslims. The influenced presenters of al-Isrāʾ wa al-Miʿrāj attract a significant number of viewers as well as their reflections. However, it is questionable in terms of reliable and quality of ḥadīth whenever they apply mix references between accepted and rejected ḥadīth in their talk on al-Isrāʾ wa al-Miʿrāj. Consequently, the netizen reflects on their talks with the mode of positive, negative and neutral attitude through the YouTube comments. Therefore, this study focuses on the trend of selected presenters in referring the ḥadīth of al-Isrāʾ wa al-Miʿrāj in the YouTube. Two Malaysian YouTube influenced presenters are selected as a case study. In order to evaluate the impact of both influenced presenters, this study examines netizen’s reflections on their talk of al-Isrāʾ wa al-Miʿrāj in the YouTube comments. This study applied the method of content analysis in evaluating the trend of both presenters in referring the ḥadīth of al-Isrāʾ wa al-Miʿrāj in the YouTube. In analysing netizens’ reflections, the classification attitude that established by Madden, Ruthven, and McMenemy (2013) is undertook as a guide to analyse YouTube video comments. The result of analysis revealed that the trend of mix references between accepted and rejected ḥadīth have been applied by both selected presenters with a significant number of those ḥadīth . Subsequently, the majority of netizen reflects positively on this trend of talk of al-Isrāʾ wa al-Miʿrāj in which the mix references between accepted and rejected ḥadīth have been applied by both presenters. The small portion of netizen reflects negatively and neutral attitude from the delivered talk. These findings signify that the netizen’s reflections on the selected talks of al-Isrāʾ wa al-Miʿrāj on YouTube mostly relies on the trend of presenters whether they refer to the authentic or the rejected ḥadīth.